5G-Based Information Platform Design of Tourist Attractions in the Context of Mobile Big Data. (13th April 2022) - Fang, Shuo
Abstract : This article aims to study the design of a tourist attraction information platform architecture based on 5G transmission technology in the context of mobile big data. It introduces the NOMA technology and the B/S mode. When introducing the nonorthogonal multiple access (NOMA) technology, it discusses the introduction and technical advantages of NOMA and puts forward the K-means algorithm, focusing on the selection of K value and distance measurement. How to measure the principle of K value NOMA technology is explained and analyzed. It can be seen that NOMA technology can effectively improve the capacity and spectrum efficiency of 5G communication system, and B/S function can reduce the cost of system maintenance and upgrade and the cost of users. In the experimental part of the article, starting from the overall design of the platform architecture, the overall design of the database, and the software and hardware platform, a tourist attraction information platform architecture based on 5G transmission technology is designed. The experimental results of this article show that people of different occupations are significantly more satisfied with the tourist attraction information platform proposed in this article than other platforms and the satisfaction is as high as 76.8%.